Reduction of crotoxin-induced neuromuscular blockade by gamma radiation - Gallacci, M.; Nunes, E. C.; Moreira, E. G.; Nascimento, N.; Rogero, JR; Vassilieff, V. S. (Elsevier B.V., 1998)
A comparative study between crotoxin and gamma irradiated crotoxin was performed on the indirectly evoked twitches and tetani of sciatic nerve-extensor digitorum longus muscle of rats. Crotoxin (3 to 14 mu g/ml) decreased the amplitude of twitches and induced a slight tetanic fade, and irradiated crotoxin did not significantly affect either twitch amplitude or tetanic tension. Since gamma radiation reduced the neurotoxicity of crotoxin it may be useful for the production of anticrotalic serum. (C) 1998 Elsevier B.V. Ltd. All rights reserved.